PLASMA HEME OXYGENASE-1 IN PATIENTS RESUSCITATED FROM OUT-OF-HOSPITAL CARDIAC ARREST. Issue 3 (March 2016) - Siren, Juuso; Vaahersalo, Jukka; Skrifvars, Markus; Pettilä, Ville; Tiainen, Marjaana; Tikkanen, Ilkka; Lakkisto, Päivi; ,
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Heme oxygenase-1 (HO-1) is an enzyme induced by hypoxia and reperfusion injury, and is associated with organ dysfunction in critically ill patients. Patients resuscitated from out-of-hospital cardiac arrest (OHCA) are subjected to hypoxemia, brain injury, and organ dysfunction. Accordingly, we studied HO-1 among these patients. A total of 143 OHCA patients resuscitated from a shockable initial rhythm and admitted to an ICU were included, with plasma HO-1 measured at ICU admission and at 24 h. We analyzed the associations between plasma HO-1 and time to return of spontaneous circulation (ROSC), 90-day mortality, and 12-month Cerebral Performance Category (CPC). HO-1 plasma concentrations were higher after OHCA compared with controls. HO-1 concentrations at admission and on day 1 associated with ROSC ( P  = 0.002 to P  = 0.003). Admission and day 1 HO-1 plasma concentrations were higher in 90-day non-survivors than in survivors ( P  = 0.017, 0.026). In addition, poor neurological outcome (CPC 3-5) was associated with higher HO-1 plasma levels at admission ( P  = 0.024). Admission plasma HO-1 levels had an AUC of 0.623 to predict 90-day mortality and an AUC of 0.611 to predict CPC 3 to 5. In conclusion, we found that higher HO-1 plasma levels are associated with longer ROSC and poor long-term outcome.